Moving Policy Theory Forward: Connecting Multiple Stream and Advocacy Coalition Frameworks to Policy Cycle Models of Analysis. Issue 1 (8th March 2016) - Howlett, Michael; McConnell, Allan; Perl, Anthony
Abstract : The stages/policy cycle, multiple streams, and Advocacy Coalition Framework (ACF) approaches to understanding policy processes, all have analytical value although also attracting substantive criticism. An obvious direction for research is to determine whether the multiple streams framework and the ACF can be refined and applied to other dimensions of policy‐making set out in the policy cycle model. This article argues that extending and modifying Kingdon's framework beyond the agenda‐setting stage is best suited to this endeavour. Doing so makes it possible to bring these three approaches into alignment and enhances our understanding, although retaining the core insights of each. Abstract : The stages/policy cycle, multiple streams (MS) and Advocacy Coalition Framework (ACF) approaches to understanding policy processes all have analytical value but also attract substantive criticism. This article provides the main elements of a new framework for understanding public policy by refining and integrating the three approaches.